Walking talking texts : a program for teaching and learning English as a second language - Murray, Fran (Frances Joan); Northern Territory. Department of Education; Northern Territory. Board of Studies (Darwin : Published by the Northern Territory Dept. of Education for the Northern Territory Board of Studies, 1995)
Walking talking texts; a program for teaching and learning english as a second language.
Cover title.
Rewrite of Walkin' talkin stories. Darwin, N.T. : Northern Territory Dept. of Education, Curriculum and Assessment Branch, 1987.
Bibliography: p. 218-220.
Written for teachers of Aboriginal students in Northern Territory schools.
Keywords: English language -- Study and teaching (Primary) -- Northern Territory -- Aboriginal speakers